High-Speed Permanent Magnet Synchronous Motor Design for Mini Unmanned Aerial Vehicle - Nory, Hayatullah; Yildiz, Ahmet (Institute of Electrical and Electronics Engineers Inc., 2024)
The rapid evolution of unmanned aerial vehicles (U A V s) has led to an increased demand for efficient and reliable propulsion systems. This study focuses on the design and development of a permanent magnet synchronous motor (PMSM) specifically designed for mini unmanned aerial vehicles. The designed PMSM has been designed to deliver 300 W output power, produce 0.28 Nm torque and operate at 10110 rpm with 28V DC supply voltage. Spoke type rotor has been preferred in PMSM design. This design not only ensures magnet integrity under high rotation speeds, but also increases the flux density in the air gap, significantly increasing torque output. Improved torque output contributes to the UAV's maneuverability, allowing rapid adaptation to evolving mission demands. © 2024 IEEE.
3rd International Conference on Power, Control and Computing Technologies, ICPC2T 2024 -- 18 January 2024 through 20 January 2024 -- Raipur -- 198443
Keywords: electrical motor design; permanent magnet synchronous motor; spoke type rotor; unmanned aerial vehicles